A model of hydrology and water quality for stormwater control measures. (September 2017) - Bell, Colin D.; Tague, Christina L.; McMillan, Sara K.
Abstract: Stormwater control measures (SCMs) are a management strategy that can reduce runoff and nitrogen (N) export from urban watersheds by creating an ecosystem that stores water and promotes N retention and removal. This work develops and explores a computer model that simulates the dynamic hydrologic and water quality processes of SCMs. Data from an SCM in Charlotte, NC was used for model calibration and validation. The hydrologic routines successfully simulated distributions of observed storm event outflow volumes and duration without calibration. Through calibration, the model reproduced observed distributions of event mean concentrations of both nitrate and ammonium in SCM outflow. Model sensitivity to varied air temperature, inflow N concentrations, and inflow volumes was determined. Scenario testing showed that deeper SCMs have greater inorganic N removal efficiencies because they have more stored volume of relatively N-deplete water, and therefore have a greater capacity to dilute relatively N-rich inflow. Highlights: Developed a process-based hydrologic and water quality model of SCMs. Added SCM routines to the watershed hydro-ecological model RHESSys. Highlighted model parameters that require calibration and empirical validation. Demonstrated how inorganic nitrogen removal changes with temperature and loading. Showed inorganic nitrogen removal efficiency increased with permanent pool depth.